On the relationship between calcified neurocysticercosis and epilepsy in an endemic village: A large‐scale, computed tomography–based population study in rural Ecuador. (29th August 2017) - Del Brutto, Oscar H.; Arroyo, Gianfranco; Del Brutto, Victor J.; Zambrano, Mauricio; García, Héctor H.
Summary: Objective: Using a large‐scale population‐based study, we aimed to assess prevalence and patterns of presentation of neurocysticercosis (NCC) and its relationship with epilepsy in community‐dwellers aged ≥20 years living in Atahualpa (rural Ecuador). Methods: In a three‐phase epidemiological study, individuals with suspected seizures were identified during a door‐to‐door survey and an interview (phase I). Then, neurologists evaluated suspected cases and randomly selected negative persons to estimate epilepsy prevalence (phase II). In phase III, all participants were offered noncontrast computed tomography (CT) for identifying NCC cases. The independent association between NCC (exposure) and epilepsy (outcome) was assessed by the use of multivariate logistic regression models adjusted for age, sex, level of education, and alcohol intake. CT findings were subsequently compared to archived brain magnetic resonance imaging in a sizable subgroup of participants. Results: Of 1, 604 villagers aged ≥20 years, 1, 462 (91%) were enrolled. Forty‐one persons with epilepsy (PWE) were identified, for a crude prevalence of epilepsy of 28 per 1, 000 population (95% confidence interval [CI] = 20.7–38.2). A head CT was performed in 1, 228 (84%) of 1, 462 participants, including 39 of 41 PWE. CT showed lesions consistent with calcified parenchymal brain cysticerci in 118 (9.6%) cases (95% CI = 8.1–11.4%). No patient had other forms of NCC. Nine of 39 PWE, as opposed to 109 of 1, 189 participants without epilepsy, had NCC (23.1% vs. 9.2%, p = 0.004). This difference persisted in the adjusted logistic regression model (odds ratio = 3.04, 95% CI = 1.35–6.81, p = 0.007). Significance: This large CT‐based study demonstrates that PWE had three times the odds of having NCC than those without epilepsy, providing robust epidemiological evidence favoring the relationship between NCC and epilepsy.